2011
DOI: 10.1089/dia.2011.0078
|View full text |Cite
|
Sign up to set email alerts
|

Orocecal Transit Time and Small Intestinal Bacterial Overgrowth in Type 2 Diabetes Patients from North India

Abstract: This study indicates that SIBO in diabetes patients may be due to delayed OCTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 19 publications
2
41
0
1
Order By: Relevance
“…Investigators have suggested that bacterial overgrowth is important to the clinical findings in patients with IBS [15] and abnormal breath testing has been seen in some patients with IBS [16]. Intestinal stasis and motility patterns are felt to predispose to the development of small intestinal bacterial overgrowth (SIBO) [17,18,19]. We employed breath hydrogen and methane testing to evaluate whether prolonged small bowel transit was associated with positive breath testing.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have suggested that bacterial overgrowth is important to the clinical findings in patients with IBS [15] and abnormal breath testing has been seen in some patients with IBS [16]. Intestinal stasis and motility patterns are felt to predispose to the development of small intestinal bacterial overgrowth (SIBO) [17,18,19]. We employed breath hydrogen and methane testing to evaluate whether prolonged small bowel transit was associated with positive breath testing.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that bacterial overgrowth may contribute to the delay of intestinal transit as confirmed by its significant improvement after eradication therapy [49]. Study by Rana et al [50] also observed that OCTT in type 2 diabetes patients with SIBO was significantly delayed (P \ 0.001) compared with type 2 diabetes patients without SIBO and they concluded that SIBO in diabetes patients may be due to delayed OCTT. In type 1 diabetes also there was a statistically significant increase in OCTT values in patients (79 ± 41 min) in comparison with controls (54 ± 17 min) (P = 0.01).…”
Section: Orocecal Transit Time and Hydrogen Breath Testsmentioning
confidence: 95%
“…Moreover, it was demonstrated that type 2 diabetes in family history and IBS were risk factors associated with the occurrence of SIBO. Gastritis proved to be a protective factor [61].…”
Section: Association Between Sibo and Other Nosological Entitiesmentioning
confidence: 96%
“…Impaired intestinal motility precedes manifestation of SIBO, which can be developed in this group of patients due to delayed orocecal transit time (OCTT) [61].…”
Section: Association Between Sibo and Other Nosological Entitiesmentioning
confidence: 99%